185k views
18 votes
Simplify the expression:
10x+10x2+2x

2 Answers

3 votes

Answer:


10x + 10x^(2) + 2x\\= 10x + 2x + 10x^(2)\\= 12x + 10x^(2)\\= \boxed{2x(6 + 5x)}

User Rajul
by
4.7k points
3 votes

Given Expression,

  • 10x + 10x² + 2x

We can also write it as,

  • 10x² + 10x + 2x

Now, Combining the like terms,

  • The like terms are 10x and 2x so,

  • 10x² + 12x

We simplified the expression.

If you want it to factorise it,

⇒10x² + 12x

⇒ 2x(5x + 6)

This is required factorised expression

User Freshtop
by
4.8k points